B cell signet-ring cell lymphoma of bone marrow. - McCluggage, W G (1995)
A case of signet-ring cell lymphoma affecting the bone marrow and diagnosed by bone marrow trephine biopsy is reported. Normal marrow was replaced totally by cells with large central vacuoles, many of which displaced the nucleus to the periphery of the cell, imparting a signet-ring appearance. Initially, the favoured morphological diagnosis was metastatic signet-ring adenocarcinoma, but on immunocytochemistry the tumour cells were strongly positive for CD45 (leucocyte common antigen) and the B cell marker CD20 (L26). Electron microscopy revealed electron-lucent vacuoles with no discernable internal structure. The tumour was classified as a high grade centroblastic lymphoma using the upgraded Kiel classification. Despite chemotherapeutic treatment, the patient died during an episode of septicaemic shock within two months of presentation.